To rewrite the given system of equations in slope-intercept form (which is \(y = mx + b\), where \(m\) is the slope and \(b\) is the y-intercept), we'll start with each equation.
-
First equation: \[ y - 5 = -4x \] To put this in slope-intercept form, add 5 to both sides: \[ y = -4x + 5 \] So, the slope-intercept form of the first equation is \[ y = -4x + 5. \]
-
Second equation: \[ 3y - 9 = -6x \] First, add 9 to both sides: \[ 3y = -6x + 9 \] Now, divide each term by 3 to solve for \(y\): \[ y = -2x + 3 \] So, the slope-intercept form of the second equation is \[ y = -2x + 3. \]
Thus, the final answers are:
- The slope-intercept form of the first equation is \(y = -4x + 5\).
- The slope-intercept form of the second equation is \(y = -2x + 3\).